Enhanced activity of Withania somnifera family-1 glycosyltransferase (UGT73A16) via mutagenesis - Singh, Somesh; Patel, Krunal A.; Sonawane, Prashant D.; Vishwakarma, Rishi K.; Khan, Bashir M. (World Journal Of Microbiology & Biotechnology, 2018)
This work used an approach of enzyme engineering towards the improved production of baicalin as well as alteration of acceptor and donor substrate preferences in UGT73A16. The 3D model of Withania somnifera family-1 glycosyltransferase (UGT73A16) was constructed based on the known crystal structures of plant UGTs. Structural and functional properties of UGT73A16 were investigated using docking and mutagenesis. The docking studies were performed to understand the key residues involved in substrate recognition. In the molecular model of UGT73A16, substrates binding pockets are located between N- and C-terminal domains. Modeled UGT73A16 was docked with UDP-glucose, UDP-glucuronic acid (UDPGA), kaempferol, isorhamnetin, 3-hydroxy flavones, naringenin, genistein and baicalein. The protein-ligand interactions showed that His 16, Asp 246, Lys 255, Ala 337, Gln 339, Val 340, Asn 358 and Glu 362 amino acid residues may be important for catalytic activity. The kinetic parameters indicated that mutants A337C and Q339A exhibited 2-3 fold and 6-7 fold more catalytic efficiency, respectively than wild type, and shifted the sugar donor specificity from UDP-glucose to UDPGA. The mutant Q379H displayed large loss of activity with UDP-glucose and UDPGA strongly suggested that last amino acid residue of PSPG box is important for glucuronosylation and glucosylation and highly specific to sugar binding sites. The information obtained from docking and mutational studies could be beneficial in future to engineer this biocatalyst for development of better ones.